2008
DOI: 10.1111/j.1099-1123.2008.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Audit Fees: Evidence from a Small Capital Market with a Joint Audit Requirement

Abstract: This paper examines audit fees paid by all 126 non-financial companies listed on the Copenhagen Stock Exchange in 2002.The Danish institutional setting is theoretically interesting because listed companies are required to use two independent auditors, and the liberal regulation of auditor independence facilitates an examination of the association between consultancy fees and audit fees. Our results indicate that de facto joint audits, where both auditors have significant stakes in the audit, reduce audit fees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 26 publications
10
67
2
3
Order By: Relevance
“…In contrast to the findings from Denmark (Thinggaard and Kiertzner, 2008), Gonthier-Besacier and Schatt (2007) show that balanced allocation between the auditors does not affect audit fees in France. They also show that companies audited by two Big 4 audit firms have a lower audit fee-size ratio compared to companies audited by other types of auditor pairs.…”
Section: Consequences Of the Joint Auditor Pair Choice And Of The Discontrasting
confidence: 50%
See 3 more Smart Citations
“…In contrast to the findings from Denmark (Thinggaard and Kiertzner, 2008), Gonthier-Besacier and Schatt (2007) show that balanced allocation between the auditors does not affect audit fees in France. They also show that companies audited by two Big 4 audit firms have a lower audit fee-size ratio compared to companies audited by other types of auditor pairs.…”
Section: Consequences Of the Joint Auditor Pair Choice And Of The Discontrasting
confidence: 50%
“…In the Danish setting, a negative association between the 'de facto' joint audit (a balanced audit fee allocation between both auditors) and audit fees can be documented for the large-client segment of the audit market (Thinggaard and Kiertzner, 2008). In contrast to the findings from Denmark (Thinggaard and Kiertzner, 2008), Gonthier-Besacier and Schatt (2007) show that balanced allocation between the auditors does not affect audit fees in France.…”
Section: Consequences Of the Joint Auditor Pair Choice And Of The Discontrasting
confidence: 43%
See 2 more Smart Citations
“…Companies with several subsidiaries are considered to be more complex than companies with few or without subsidiaries. A significant proportion of previous studies observed positive relationship between corporate complexity and audit fees (Simunic, 1980;Brinn et al, 1994;Cameran, 2005;Joshi & Bastaki, 2000;Clatworthy & Peel, 2006;Thinggaard & Kiertzner, 2008;Vermeer et al, 2009;Ellis & Booker, 2011;Verbruggen et al, 2011). The main reasons advanced in the literature to explain such a relationship is that greater number of subordinate financial statements require more audit time and greater expertise to ensure the accuracy of the consolidated financial statements (Sandra & Patrick, 1996).…”
Section: Complexitymentioning
confidence: 99%